2017
DOI: 10.1111/bmsp.12117
|View full text |Cite
|
Sign up to set email alerts
|

A semi‐parametric within‐subject mixture approach to the analyses of responses and response times

Abstract: In item response theory, modelling the item response times in addition to the item responses may improve the detection of possible between- and within-subject differences in the process that resulted in the responses. For instance, if respondents rely on rapid guessing on some items but not on all, the joint distribution of the responses and response times will be a multivariate within-subject mixture distribution. Suitable parametric methods to detect these within-subject differences have been proposed. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 53 publications
2
56
0
Order By: Relevance
“…In the simulation study, we compared the performance of the unweighted SW test, the unweighted KS test, and the weighted KS test. Data are simulated according to nine different scenarios, mostly based on Molenaar et al (2018) who found biased modeling results of the hierarchical mixture model in the case of nonnormality. The first three scenarios concern Markov mixture models that include Markov-dependent item states, the next three scenarios concern mixture models with independent item states, and the final three scenarios are generated according to a baseline model that does not include item states (i.e., a static model without mixtures).…”
Section: Methodsmentioning
confidence: 99%
“…In the simulation study, we compared the performance of the unweighted SW test, the unweighted KS test, and the weighted KS test. Data are simulated according to nine different scenarios, mostly based on Molenaar et al (2018) who found biased modeling results of the hierarchical mixture model in the case of nonnormality. The first three scenarios concern Markov mixture models that include Markov-dependent item states, the next three scenarios concern mixture models with independent item states, and the final three scenarios are generated according to a baseline model that does not include item states (i.e., a static model without mixtures).…”
Section: Methodsmentioning
confidence: 99%
“…A related yet conceptually distinct strand of work [12,13,14,15] considers responses as coming from a mixture of response processes. In particular, responses are generated by either "fast" or "slow" processes and the relevant item characteristics are allowed to vary as a function of the process.…”
Section: Psychological Approachesmentioning
confidence: 99%
“…Unfortunately, approaches that are capable of handling one form of contamination do not work well for the other form of contamination (Alqallaf et al ., ). This is apparent for the mixture models that require strong assumptions about the form of contamination and fail if these assumptions are not met (Molenaar et al ., ; Ranger & Kuhn, ). Mixture models have more limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The responses and response times in the regular response mode are usually modelled with the hierarchical model of van der Linden (). The responses and response times in the irregular response mode are assumed to be faster and are modelled differently; for specific variants of such mixture models see Meyer (), Molenaar, Bolsinova, and Vermunt (), Wang and Xu () and Wang et al . ().…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation